Minimizing sulphur dioxide injury in table grapes (Vitis vinifera) for export by pre-harvest benomyl sprays - SAWANT, S D; SAWANT, INDUS; BANERJEE, KAUSHIK (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 1997-98 and 1998-99 to study the effect of pre-harvest sprays of benomyl or ipordione in controlling post-harvest decay in table grapes (Vitis vinifera L.) at reduced dose of SO2 generators. The pre-harvest spray of benomyl at 0.05-0.10% at 20 or 10 days before harvest, effectively controlled post-harvest decay (0.04-2.78% decayed berries after 30 days of cold storage and 3 days on shelf at 30-35oC) at 2.3 g Na2S2O5/5 kg grapes.Â  The SO2 injury at this dose of Na2 S2O2 was within acceptable limits (1-3%). Further, the residues of benomyl at harvest and after cold storage were found below the maximum residue limit.